Electrocardiographic and echocardiographic features in patients with major arterial vascular disease assigned to surgical revascularization. Issue 6 (2nd November 2019) - Tsialtas, Dimitri; Bolognesi, Maria Giulia; Assimopoulos, Stephania; Volpi, Riccardo; Bolognesi, Roberto
Abstract: Background: We aimed to depict the electrocardiographic and echocardiographic aspects in patients before elective major vascular surgery. Methods: We evaluated through standard 12 lead electrocardiography and transthoracic echocardiography 469 patients with asymptomatic large abdominal aortic aneurysm (AAA), 334 with critical carotid stenosis (CAS), and 238 with advanced peripheral artery disease (PAD) before surgical revascularization. Results: Patients with AAA were predominantly males ( p < .001) with normal sinus rhythm ( p = .026), were more affected by atrioventricular block ( p = .033) and left anterior fascicular block ( p < .001). They also presented larger aortic root size ( p < .001) and septal hypertrophy ( p = .036), in addition, atrial fibrillation was less frequent in the same group ( p = .023). Patients with CAS were of older age ( p < .001) with a substantial number of females ( p < .001). They presented less left ventricular segmental kinetic disorders and fewer dilated ventricles ( p = .004 and p < .001 respectively). Finally, those with PAD had reduced septal and posterior wall thickness ( p < .01, p = .009 respectively), greater mitral and aortic annular calcification ( p < .001), and were more affected by previous myocardial infarction ( p < .001). The PR interval, left anterior fascicular block and aortic root size were independently associated with aneurysm, previous myocardial infarction with PAD, while smaller left ventricular end systolic volumes with carotid artery stenosis. Conclusions: Patients with AAA were mostly affected by cardiac conduction disorders, septal hypertrophy, aortic root dilation and less affected by atrial fibrillation. Patients with CAS were older with more normal sized ventricles, whereas, previous myocardial infarction was most common amongst patients with peripheral artery disease.